Thermoelastic Effect During Tensile Cyclic Deformation - Pieczyska, E.A.; Gadaj, S.P. (Engineering Transactions, 1997)
Experimental results of the effects of thermomechanical coupling occurring in metal during a cyclic tension test are presented. In each cycle the thermoelastic effect, i.e. the decrease of temperature in the initial stage of deformation was observed. Afterwards the specimen was heated up due to initiation and evolution of the mechanisms of plastic deformation. The change of character of the temperature behaviour of the sample subjected to loading allowed us to determine the limit between the elastic and plastic regime. Moreover, it was noticed that the temperature characteristics vs. stress manifested the transition from the elastic to plastic deformation more distinctly than the stress-strain relations.